Verdade e Democracia: leitura do debate entre Richard Rorty e Jürgen Habermas - Vergolino, Eduardo Barbosa (2009)
The present work has the principal objective highlighted in the differences and similarities between the philosophers Richard Rorty and Jürgen Habermas about the concept of truth established for both. First, we present the Rorty s thought about truth, passing by the idea of etnocentrism and about the contingency that the language has beyond the idea of a democracy, fundamental subject for we understand his idea of truth. Second, we approach the habermasian idea of truth pointing his concept like something universal and transcendental to cultural contexts and temporal. His idea of life world intersubjectively shared. The appearance of one pos-metaphysic linguistic turns capable of changes in the main point of philosophy and his idea of democracy. Finally, a little sketch of one ethic of the discourse capable of join all necessary characteristics for the formation of one concept of truth universal and transcendental.